ELECTRIC FIELD CONTOURS IN NON-UNIFORM ELECTRODE SHAPE - Umiati, Ngurah Ayu Ketut; Facta, Mochammad (BERKALA FISIKA, 2020)
Silent discharge is well known method to initiate plasma reaction because initial  discharge is easily triggered by implementing high voltage to the pair of coupled electrodes with a distance. However,  it  is  very  difficult  to  determine  the  exact  amount  of  the  voltage  that  initiates  the discharge.  There  are  many  factors  influence  the  condition  of  initial  discharge  such  as dimensions,  type  and  geometrical  shapes  of  electrode,  thickness  of  insulation,  and  type  of electric field inside the gap between the electrodes. To obtain lower initial discharge voltage, it is urgent to find the best electrode shape producing electric field contours in line with electron emission triggering. This work examines the behavior of electric field and the applied voltage surrounding  electrodes  by  investigating  the  mathematical  expression  for  given  voltage  and generated  electric  field.  The  mathematical  relationship  then  gives  a  basis  of  theoretical background for electric field contours of two shape electrodes. It is also well known that among many electrodes, the non-uniform geometrical shape is preferred to initiate electric field easily. In this study, a hole shape and a bulge type electrode are investigated.Keywords: silent discharge, electric field, differential equation, electrode shape